Tanzania Health Policy Note : Reasons and Consequences of Low Budget Execution - Ally, Mariam; Piatti-Funfkirchen, Moritz (World Bank, Washington, DC, 2021)
This is the second in a series of health policy notes that address critical health finance related questions in Tanzania. They are issued as part of a larger public expenditure review exercise. The audience is government, civil society and the development partner community with the aim to initiate a dialogue around key health finance issues and present recommendations to government. This policy note raises budget execution in health as a problem and discusses reasons behind low rates and the consequences for service delivery.